1997
DOI: 10.1073/pnas.94.25.13730
|View full text |Cite
|
Sign up to set email alerts
|

From tropics to tundra: Global convergence in plant functioning

Abstract: Despite striking differences in climate, soils, and evolutionary history among diverse biomes ranging from tropical and temperate forests to alpine tundra and desert, we found similar interspecific relationships among leaf structure and function and plant growth in all biomes. Our results thus demonstrate convergent evolution and global generality in plant functioning, despite the enormous diversity of plant species and biomes. For 280 plant species from two global data sets, we found that potential carbon gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

125
2,084
34
40

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 2,130 publications
(2,331 citation statements)
references
References 33 publications
125
2,084
34
40
Order By: Relevance
“…Higher terpene contents are compatible with a fast return strategy of "leaf economics spectrum" based on a higher photosynthetic capacity, higher nutrient content, lower LMA, and faster return on investment in foliage (Wright et al, 2004). These traits help to explain the success of invasive plant species (Pattison et al, 1998;Baruch and Goldstein, 1999;Funk and Vitousek, 2007) since they can contribute to faster growth rates for invaders and confer a competitive advantage over native species (Reich et al, 1997;Blumenthal and Hufbauer, 2007). have observed these faster returns from their investments in nutrients and dry mass in leaves, and these higher contents of most nutrients in these alien species in Oahu (Hawaii).…”
Section: Discussionmentioning
confidence: 98%
“…Higher terpene contents are compatible with a fast return strategy of "leaf economics spectrum" based on a higher photosynthetic capacity, higher nutrient content, lower LMA, and faster return on investment in foliage (Wright et al, 2004). These traits help to explain the success of invasive plant species (Pattison et al, 1998;Baruch and Goldstein, 1999;Funk and Vitousek, 2007) since they can contribute to faster growth rates for invaders and confer a competitive advantage over native species (Reich et al, 1997;Blumenthal and Hufbauer, 2007). have observed these faster returns from their investments in nutrients and dry mass in leaves, and these higher contents of most nutrients in these alien species in Oahu (Hawaii).…”
Section: Discussionmentioning
confidence: 98%
“…2 and Extended Data Table 1 were robust with respect to the selection of traits and species and representative for vascular plants, we conducted a number of analyses: exclusion of gymnosperms and pteridophytes ('angiosperms only'), exclusion of individual traits, and comparison to a gap-filled dataset representing about 15% of extant vascular plant species worldwide. The trait exclusion tests excluded the following individual traits, one at a time: LMA, N mass and SSD, because analyses indicated that LMA and N mass , although providing information on different aspects of leaf function (see Methods), are both part of the leaf economic spectrum 7,10 , and SSD and plant height both reflect plant size when woody and herbaceous plants are considered together. To test if the results of the multivariate analysis presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2a, 'H-SM' , more strongly associated with PC1 than PC2). The other (upper left to lower right in Fig 2a, 'LMA-N mass ' , more strongly associated with PC2 than PC1) runs from species with cheaply constructed, 'acquisitive' leaves (low-LMA, nitrogen-rich) to species with 'conservative' leaves (high-LMA, nitrogen-poor) that are expected to have longer leaf lifespan and higher survival in the face of abiotic and biotic hazards 7,10,36 . Stem specific density (SSD) and leaf area (LA) also load heavily on the plane and are correlated with both the H-SM and the LMA-N mass dimensions (Fig 2a, Extended Data Table 1).…”
Section: Main Trends Of Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed development and discussion of the underlying concepts behind the light use efficiency model are described in extensive studies and reviews by Field (1991), Reich et al (1997) and .…”
Section: Light Use Efficiency Based Modeling Of Primary Productionmentioning
confidence: 99%